Amorphous polymer (P) comprising segments (S1), (S2) and (S3)
By preparing amorphous polymers with specific segment structures, the problems of poor solubility in conventional solvents and insufficient tolerance to organic solvents are solved, and good solubility and tolerance are achieved, and the product is transparent.
Patent Information
- Application Number
- CN202080025899.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-01
- Filing Date
- 2020-03-10
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2040-03-10
AI Technical Summary
The existing polyarylene ether sulfone polymers have poor solubility in conventional solvents and are insufficient tolerate organic solvents, resulting in problems in the film preparation process.
Amorphous polymers containing specific segment structures, specifically including 80 to 90 mol% of sulfone-containing segments (S1) and 10 to 20 mol% of ketone-containing segments (S2) to improve their solubility in conventional solvents and tolerance to organic solvents.
Good solubility of the amorphous polymer in conventional solvents and good chemical resistance to organic solvents are achieved, while the product is transparent.
Smart Images

Figure BDA0003285304480000021 
Figure BDA0003285304480000031 
Figure BDA0003285304480000032
Abstract
Description
[0001] The present invention relates to an amorphous polymer (P), which comprises a segment (S1) containing a sulfone group, a segment (S2) containing a ketone group and a segment (S3) containing a polyarylene group. In addition, the present invention relates to a method for preparing the amorphous polymer (P), a composition comprising the amorphous polymer (P) and an article comprising the amorphous polymer (P).
[0002] Polyarylene ether sulfone polymers are high-performance thermoplastics because they have high heat resistance, good mechanical properties and inherent flame retardancy (EM Koch, H.-M. Walter, Kunststoffe 80 (1990) 1146; E. Kunststoffe 80, (1990) 1149, N. Inchaurondo-Nehm, Kunststoffe 98, (2008) 190). Polyarylene ether has a high degree of biocompatibility and is therefore also used as a material for forming a dialysis membrane (NA Hoenich, KP Katapodis, Biomaterials 23 (2002) 3853).
[0003] The polyarylene ether sulfone polymers can be formed, inter alia, by the hydroxide process, in which a salt is first formed from a dihydroxy component and a hydroxide, or by the carbonate process.
[0004] General information on the formation of polyarylene ether sulfone polymers by the hydroxide process is found, inter alia, in RN Johnson et al., J. Polym. Sci. A-1 5 (1967) 2375, while the carbonate process is described in JEMcGrath et al., Polymer 25 (1984) 1827.
[0005] The formation of polyarylene ether sulfone polymers from aromatic dihalogen compounds and aromatic bisphenols or their salts in the presence of one or more alkali metal or ammonium carbonates or bicarbonates in an aprotic solvent is known to those skilled in the art and is described in EP-A 297 363, for example.
[0006] High performance thermoplastics such as poly(arylene ether sulfone) polymers are formed by polycondensation reactions, which are typically carried out at high reaction temperatures in dipolar aprotic solvents such as dimethylformamide (DMF), dimethylacetamide (DMAc), sulfolane, dimethyl sulfoxide (DMSO), and N-methyl-2-pyrrolidone (NMP).
[0007] The application of poly(arylene ether sulfone) polymers in polymer membranes is becoming increasingly important.
[0008] Poly(arylene ether sulfone) polymers are amorphous. Compared to semi-crystalline polymers such as polyphenylene sulfide, amorphous poly(arylene ether sulfone) polymers exhibit poor resistance to organic fluids such as FAM B (toluene-containing test fluid) or Skydrol (a mixture of phosphate esters).
[0009] In order to improve the resistance to organic solvents, EP 2 225 328 describes semi-crystalline polymers containing sulfonyl groups, keto groups and polyarylene groups. According to EP 2 225 328, 4,4'-dichlorodiphenyl sulfone, 4,4'-dichlorobenzophenone and 4,4'-dihydroxybiphenyl are preferably reacted in diphenyl sulfone to obtain semi-crystalline polymers. According to EP 2 225 328, the melting temperature of the semi-crystalline polymer is greater than 300° C. However, the polymers described in EP 2 225 328 show poor solubility in conventional solvents such as N-methylpyrrolidone (NMP) or dimethylacetamide (DMAc), so problems arise when using these polymers to prepare membranes by phase inversion.
[0010] Furthermore, the polymers described in EP 2 225 328 are not transparent.
[0011] JP 2008-37897 discloses a sulfonic acid group-containing photocrosslinkable polymer which may contain a sulfone group, a ketone group and a polyarylene group.
[0012] The article “Synthesis and characterization of novel poly(arylether sulfone ketone)s containing phthalazinone and biphenyl moieties” by LH Xiao et al., Chin. Chem. Lett. 19 (2008) 227 discloses the preparation of amorphous poly(phthalazinone ether sulfone ketone)s by reacting, inter alia, 4,4′-diphenol (BP), 4,4′-dichlorodiphenyl sulfone (DCS) and 4,4′-difluorobenzophenone (DFK).
[0013] CN 103613763 and CN 104497300 describe the synthesis of semicrystalline high-flow polyphenylene ether sulfone ketone containing sulfone groups, ketone groups and polyarylene groups.
[0014] GB 2 241 245 discloses amorphous polysulfone ether ketone polymers comprising sulfone groups, keto groups and polyarylene groups, wherein the molar ratio of sulfone groups to keto groups is 1:1.
[0015] Therefore, the object of the present invention is to provide an amorphous polymer (P) which does not have the disadvantages of the prior art or has them only in a reduced form. The amorphous polymer (P) should show good chemical resistance to organic solvents such as FAM B or Skydrol. Another object of the present invention is to provide a process for preparing the amorphous polymer (P). The process should preferably be carried out in a short reaction time.
[0016] This object is achieved by an amorphous polymer (P) comprising:
[0017] The following chain segment (S1)
[0018]
[0019] The following chain segment (S2)
[0020]
[0021] The following chain segment (S3)
[0022]
[0023] The object is further achieved by an amorphous polymer (P) comprising:
[0024] The following chain segment (S1)
[0025]
[0026] The following chain segment (S2)
[0027] and
[0028] The following chain segment (S3)
[0029]
[0030] wherein the amorphous polymer (P) comprises:
[0031] 80 to 90 mol % of segment (S1), and
[0032] 10 to 20 mol% of segment (S2),
[0033] The total number of moles of the segments (S1) and (S2) contained in the amorphous polymer (P) is calculated.
[0034] Surprisingly, it was found that the amorphous polymer (P) exhibits good chemical resistance to organic solvents such as FAM B or Skydrol, and the amorphous polymer exhibits good solubility in conventional solvents such as N-methylpyrrolidone (NMP) or dimethylacetamide (DMAc). In addition, articles made from the amorphous polymer (P) are transparent.
[0035] The present invention will be described in more detail below.
[0036] The amorphous polymer (P) of the present invention generally comprises the segments (S1), (S2) and (S3) defined above. The segments (S1), (S2) and (S3) may be present in the main chain, chain ends and / or repeating units of the amorphous polymer (P) of the present invention. Preferably, the segments (S1), (S2) and (S3) are contained in the repeating units of the amorphous polymer (P). The amorphous polymer (P) of the present invention is preferably derived from two or more repeating units. More preferably, the amorphous polymer (P) is derived from two different repeating units.
[0037] In a preferred embodiment, the amorphous polymer (P) comprises 80 to 90 mol %, more preferably 80.1 to 89 mol %, even more preferably 80.2 to 88 mol %, particularly preferably 80.3 to 87 mol % and most preferably 80.4 to 86.5 mol % of segments (S1) and 10 to 20 mol %, more preferably 11 to 19.9 mol %, even more preferably 12 to 19.8 mol %, particularly preferably 13 to 19.7 mol % and most preferably 13.5 to 19.6 mol % of segments (S2), in each case based on the total number of moles of segments (S1) and segments (S2) contained in the amorphous polymer (P).
[0038] Therefore, another object of the present invention is such an amorphous polymer (P) comprising:
[0039] 80 to 90 mol % of segment (S1), and
[0040] 10 to 20 mol% of segment (S2),
[0041] The total number of moles of the segments (S1) and (S2) contained in the amorphous polymer (P) is calculated.
[0042] In another preferred embodiment, the ratio of the molar number of segments (S1) contained in the amorphous polymer (P) to the molar number of segments (S2) is from 4 to 9, more preferably from 4.02 to 8.09, even more preferably from 4.05 to 7.33, particularly preferably from 4.08 to 6.69 and most preferably from 4.10 to 6.41.
[0043] In a preferred embodiment, the term "amorphous" of the amorphous polymer (P) of the present invention is defined as follows. In a preferred embodiment, the term "amorphous" means that the amorphous polymer (P) has a melting enthalpy ΔH of 0 to 5 W / g, preferably 0 to 4 W / g, even more preferably 0 to 3 W / g, particularly preferably 0 to 2.5 W / g, and most preferably 0 to 2 W / g. m In another most preferred embodiment, the amorphous polymer (P) does not exhibit a melting point. In this case, the melting enthalpy ΔH m is 0. The abbreviation W / g stands for Watt / gram.
[0044] In a preferred embodiment, the term "amorphous" of the amorphous polymer (P) of the present invention is further defined as follows. In a preferred embodiment, the term "amorphous" also means that the amorphous polymer (P) has a crystallization enthalpy ΔH of 0 to 5 W / g, preferably 0 to 4 W / g, even more preferably 0 to 3 W / g, particularly preferably 0 to 2.5 W / g, and most preferably 0 to 2 W / g c In another most preferred embodiment, the amorphous polymer (P) does not show crystallization points. In this case, the crystallization enthalpy ΔH m is 0. The abbreviation W / g stands for Watt / gram.
[0045] Melting enthalpy ΔH m (if any) and crystallization enthalpy ΔH c (if any) determined by DSC (differential scanning calorimetry), starting from 20°C, a sample of the amorphous polymer (P) is heated at a rate of 20 K / min to a temperature of 360°C, then cooled to 20°C at a rate of >100 K / min, then heated a second time to 360°C at a rate of 20 K / min, then cooled a second time to 20°C at a rate of >100 K / min, wherein the melting enthalpy ΔH is determined during the second heating and the second cooling m and crystallization enthalpy ΔH c .
[0046] If an amorphous polymer (P) is annealed at 250 °C for 0.5 h, in some cases a small phase transition (melting point) can be detected by DSC, showing the melting enthalpy ΔH m In addition, if the amorphous polymer (P) is annealed at 250°C for 0.5 h, in some cases a small phase transition (crystallization point) can be detected by DSC, showing the crystallization enthalpy ΔH c The range is 0.1 to <4 W / g.
[0047] In a preferred embodiment, if the amorphous polymer (P) is not annealed by DSC (using the method described above), no melting point can be detected. In addition, in a preferred embodiment, if the amorphous polymer (P) is not annealed by DSC (using the method described above), no crystallization point can be detected.
[0048] Repeating unit (RU1)
[0049] The amorphous polymer (P) described above may comprise a repeating unit (RU1), which can be obtained by a reaction between at least one aromatic dihalogen compound (D1,1) comprising at least one segment (S1) and at least one aromatic dihydroxy compound (aDHy1). The aromatic dihalogen compound (D1,1) is also referred to as an "aromatic dihalogen sulfone compound (D1,1)". These terms are used synonymously and have the same meaning. The repeating unit (RU1) comprises a segment (S1). The repeating unit (RU1) may comprise two or more segments (S1). In a preferred embodiment, the repeating unit (RU1) comprises one segment (S1). The repeating unit (RU1) may also comprise a segment (S2) and / or a segment (S3). It may also be free of segments (S2) and segments (S3). In a preferred embodiment, the repeating unit (RU1) comprises a segment (S1) and a segment (S2) or a segment (S3). In a more preferred embodiment, the repeating unit (RU1) comprises segment (S1) and segment (S3).
[0050] In a particularly preferred embodiment, the repeating unit (RU1) consists of segment (S1) and segment (S2) or segment (S3). In a most preferred embodiment, the repeating unit (RU1) consists of segment (S1) and segment (S3).
[0051] The aromatic dihalogen compound (D1,1) from which the repeating unit (RU1) is obtainable is preferably 4,4'-dihalodiphenyl sulfone or 4,4'-bis[(4-chlorophenyl)sulfonyl]-1,1'-biphenyl. More preferably, the aromatic dihalogen compound (D1,1) is 4,4'-dihalodiphenyl sulfone. Still more preferably, the 4,4'-dihalodiphenyl sulfone is selected from 4,4'-dichlorodiphenyl sulfone, 4,4'-difluorodiphenyl sulfone and mixtures thereof, wherein 4,4'-dichlorodiphenyl sulfone is particularly preferred.
[0052] The aromatic dihydroxy compound (aDHy1) from which the repeating unit (RU1) is obtainable is preferably 4,4′-diphenol, 4,4′-dihydroxybenzophenone or a mixture thereof, with 4,4′-diphenol being particularly preferred.
[0053] In a particularly preferred embodiment, the repeating unit (RU1) is obtained by reaction of the monomers 4,4'-dichlorodiphenyl sulfone and 4,4'-diphenol.
[0054] Repeating unit (RU2)
[0055] The amorphous polymer (P) described above may comprise a repeating unit (RU2), which can be obtained by a reaction between at least one aromatic dihalogen compound (D2,1) comprising at least one segment (S2) and at least one aromatic dihydroxy compound (aDHy2). The aromatic dihalogen compound (D2,1) is also referred to as "aromatic dihalogen ketone (D2,1)". These terms are used synonymously and have the same meaning. The repeating unit (RU2) comprises a segment (S2). The repeating unit (R2) may comprise two or more segments (S2). In a preferred embodiment, the repeating unit (RU2) comprises one segment (S2). The repeating unit (RU2) may also comprise a segment (S1) and / or a segment (S3). It may also be free of segments (S1) and segments (S3). In a preferred embodiment, the repeating unit (RU2) comprises a segment (S2) and a segment (S1) or a segment (S3). In a more preferred embodiment, the repeating unit (RU2) comprises segment (S2) and segment (S3).
[0056] In a particularly preferred embodiment, the repeating unit (RU2) consists of segment (S2) and segment (S1) or segment (S3). In a most preferred embodiment, the repeating unit (RU2) consists of segment (S2) and segment (S3).
[0057] The aromatic dihalogen compound (D2,1) from which the repeating unit (RU2) is obtainable is preferably a 4,4'-dihalogenobenzophenone. More preferably, the 4,4'-dihalogenobenzophenone is selected from 4,4'-dichlorobenzophenone, 4,4'-difluorobenzophenone and mixtures thereof, wherein 4,4'-dichlorobenzophenone is particularly preferred.
[0058] The aromatic dihydroxy compound (aDHy2) from which the repeating units (RU2) are obtainable is preferably 4,4'-diphenol, 4,4'-dihydroxybenzophenone or a mixture thereof, with 4,4'-diphenol being particularly preferred.
[0059] In a particularly preferred embodiment, the repeating unit (RU2) is obtained by reaction of the monomers 4,4'-dichlorobenzophenone and 4,4'-diphenol.
[0060] Repeating unit (RU3)
[0061] The amorphous polymer (P) described above may comprise a repeating unit (RU3), which can be obtained by the reaction between at least one aromatic dihydroxy compound (D2,2) comprising at least one segment (S2) and at least one aromatic dihalogen compound (aDHa1). The repeating unit (RU3) comprises a segment (S2). The repeating unit (RU3) may comprise two or more segments (S2). In a preferred embodiment, the repeating unit (RU3) comprises one segment (S2). The repeating unit (RU3) may also comprise a segment (S1) and / or a segment (S3). It may also be free of a segment (S1) and a segment (S3). In a preferred embodiment, the repeating unit (RU3) comprises a segment (S2) and a segment (S1) or a segment (S3). In a more preferred embodiment, the repeating unit (RU3) comprises a segment (S2) and a segment (S1).
[0062] In a particularly preferred embodiment, the repeating unit (RU3) consists of segment (S2) and segment (S1) or segment (S3). In a most preferred embodiment, the repeating unit (RU3) consists of segment (S2) and segment (S1).
[0063] The aromatic dihydroxy compound (D2,2) from which the repeating unit (RU3) is obtainable is preferably 4,4′-dihydroxybenzophenone.
[0064] The aromatic dihalogen compound (aDHa1) is preferably 4,4'-dihalogenated diphenyl sulfone or 4,4'-bis[(4-chlorophenyl)sulfonyl]-1,1'-biphenyl. More preferably, the aromatic dihalogen compound (aDHa1) is 4,4'-dihalogenated diphenyl sulfone. Still more preferably, the 4,4'-dihalogenated diphenyl sulfone is selected from 4,4'-dichlorodiphenyl sulfone, 4,4'-difluorodiphenyl sulfone and a mixture thereof, wherein 4,4'-dichlorodiphenyl sulfone is particularly preferred.
[0065] In a particularly preferred embodiment, the repeating unit (RU3) is obtained by reaction of the monomers 4,4'-dihydroxybenzophenone and 4,4'-dichlorodiphenyl sulfone.
[0066] Repeating unit (RU4)
[0067] The amorphous polymer (P) described above may comprise a repeating unit (RU4), which can be obtained by the reaction between at least one aromatic dihydroxy compound (D3,1) comprising at least one segment (S3) and at least one aromatic dihalogen compound (aDHa2). The repeating unit (RU4) comprises a segment (S3). The repeating unit (R4) may comprise two or more segments (S3). In a preferred embodiment, the repeating unit (RU4) comprises one segment (S3). The repeating unit (RU4) may also comprise a segment (S1) and / or a segment (S2). It may also be free of a segment (S1) and a segment (S2). In a preferred embodiment, the repeating unit (RU4) comprises a segment (S3) and a segment (S1) or a segment (S2). In a more preferred embodiment, the repeating unit (RU4) comprises a segment (S3) and a segment (S1).
[0068] In a particularly preferred embodiment, the repeating unit (RU4) consists of segment (S3) and segment (S1) or segment (S2). In a most preferred embodiment, the repeating unit (RU4) consists of segment (S3) and segment (S1). In this case, the repeating unit (R4) is equal to the repeating unit (RU1).
[0069] The aromatic dihydroxy compound (D3,1) from which the repeating unit (RU4) is obtainable is preferably 4,4′-diphenol.
[0070] The aromatic dihalogen compound (aDHa2) is preferably 4,4'-dihalogenated diphenyl sulfone or 4,4'-bis[(4-chlorophenyl)sulfonyl]-1,1'-biphenyl. More preferably, the aromatic dihalogen compound (aDHa2) is 4,4'-dihalogenated diphenyl sulfone. Still more preferably, the 4,4'-dihalogenated diphenyl sulfone is selected from 4,4'-dichlorodiphenyl sulfone, 4,4'-difluorodiphenyl sulfone and a mixture thereof, wherein 4,4'-dichlorodiphenyl sulfone is particularly preferred.
[0071] In a particularly preferred embodiment, the repeating unit (RU4) is obtained by reaction of the monomers 4,4'-diphenol and 4,4'-dichlorodiphenyl sulfone. In this case, the repeating unit (R4) is equal to the repeating unit (RU1).
[0072] The polydispersity (Q) of the amorphous polymer (P) is generally ≤5, preferably ≤4.5.
[0073] Polydispersity (Q) is defined as M w :M n The ratio (M w / M nIn a preferred embodiment, the polydispersity (Q) of the amorphous polymer (P) is from 2.0 to ≤5 and preferably from 2.1 to ≤4.5.
[0074] The weight average molecular weight (M) was measured by gel permeation chromatography. W ) and number average molecular weight (M n ).
[0075] The polydispersity (Q) and the average molecular weight of the amorphous polymer (P) were measured using gel permeation chromatography. In the measurement, dimethylacetamide (DMAc) was used as solvent and narrow distribution polymethyl methacrylate was used as standard.
[0076] The weight average molecular weight (M) of the amorphous polymer (P) obtainable by the process of the present invention is W ) is generally 30,000 to 120,000 g / mol, preferably 40,000 to 100,000 g / mol and more preferably 45,000 to 80,000 g / mol. The weight average molecular weight (M) is measured using gel permeation chromatography (GPC). W ). The measurement was performed as described above.
[0077] The terminal groups of the amorphous polymer (P) are usually halogen groups, especially chlorine groups, or etherified groups, especially alkyl ether groups. The etherified terminal groups can be obtained by reacting the terminal OH / phenoxy groups with suitable etherifying agents.
[0078] Examples of suitable etherifying agents are monofunctional alkyl or aryl halides, such as C1-C6 alkyl chlorides, bromides or iodides, preferably methyl chloride, or benzyl chloride, benzyl bromide or benzyl iodide, or mixtures thereof. The terminal groups of the polyarylene ether sulfone polymers of the present invention are preferably halogen groups, especially chlorine; and alkoxy groups, especially methoxy groups, aryloxy groups, especially phenoxy groups or benzyloxy groups.
[0079] The ratio of the total weight of the repeating units (RU1), (RU2), (RU3) and (RU4) comprised in the amorphous polymer (P) to the total weight of the amorphous polymer (P) is advantageously greater than 0.7. This ratio is preferably greater than 0.8, more preferably greater than 0.9, still more preferably greater than 0.95. Most preferably, the polymer of the invention does not comprise further repeating units than the repeating units (RU1), (RU2), (RU3) and (RU4).
[0080] In a preferred embodiment, the ratio of the total weight of repeating units (RU1), (RU2) and / or (RU3) comprised in the amorphous polymer (P) to the total weight of the amorphous polymer (P) is advantageously greater than 0.7. This ratio is preferably greater than 0.8, more preferably greater than 0.9, still more preferably greater than 0.95. Most preferably, the polymer of the invention does not comprise further repeating units than repeating units (RU1), (RU2) and / or (RU3).
[0081] In another more preferred embodiment, the ratio of the total weight of the repeating units (RU1) and (RU2) comprised in the amorphous polymer (P) to the total weight of the amorphous polymer (P) is advantageously greater than 0.7. This ratio is preferably greater than 0.8, more preferably greater than 0.9, still more preferably greater than 0.95. Most preferably, the polymer of the present invention does not comprise further repeating units than the repeating units (RU1) and (RU2).
[0082] In a preferred embodiment, repeating unit (RU1) is obtainable by reaction of monomers 4,4'-dichlorodiphenyl sulfone and 4,4'-diphenol, repeating unit (RU2) is obtainable by reaction of monomers 4,4'-dichlorobenzophenone and 4,4'-diphenol, and / or repeating unit (RU3) is obtainable by reaction of monomers 4,4'-dihydroxybenzophenone and 4,4'-dichlorodiphenyl sulfone.
[0083] In a preferred embodiment, the amorphous polymer (P) is obtainable by reacting the compounds defined above for preparing repeating units (RU1), (RU2) and / or (RU3), wherein the above statements and preferences apply correspondingly.
[0084] In a preferred embodiment, the amorphous polymer (P) can be obtained by reacting:
[0085] An aromatic dihalogen compound (D1,1) and an aromatic dihydroxy compound (aDHy1), and
[0086] Aromatic dihalogen compound (D2,1) and aromatic dihydroxy compound (aDHy2),
[0087] wherein the aromatic dihydroxy compound (aDHy1) and (aDHy2) are both 4,4'-diphenol, wherein the aromatic dihalogen compound (D1,1) is 4,4'-dichlorodiphenyl sulfone, and wherein the molar amount of the aromatic dihalogen compound (D1,1) used in the reaction is 80 to 90 mol%, more preferably 80.1 to 89 mol%, even more preferably 80.2 to 88 mol%, particularly preferably 80.3 to 87 mol% and most preferably 80.4 to 86.5 mol%,
[0088] and wherein the molar amount of the aromatic dihalogen compound (D2,1) used in the reaction is 10 to 20 mol%, more preferably 11 to 19.9 mol%, even more preferably 12 to 19.8 mol%, particularly preferably 13 to 19.7 mol% and most preferably 13.5 to 19.6 mol%,
[0089] In each case, this is based on the total molar amount of the aromatic dihalogen compound (D1,1) and the aromatic dihalogen compound (D2,1) used in the reaction.
[0090] In another preferred embodiment, the number of moles of the aromatic dihalogen compound (D1,1) used in the reaction from which the amorphous polymer (P) is obtainable is from 4 to 9, more preferably from 4.02 to 8.09, even more preferably from 4.05 to 7.33, particularly preferably from 4.08 to 6.69, and most preferably from 4.10 to 6.41, relative to the number of moles of the dihalogen compound (D2,1).
[0091] Another aspect of the present invention is a composition comprising an amorphous polymer (P). In a preferred embodiment, the composition may comprise at least one additional ingredient. The additional ingredients may preferably be selected from other polymers, solvents, fillers, additives, colorants, reinforcing agents, lubricants, thermal stabilizers, processing aids, antistatic agents, antioxidants and flame retardants. Suitable other polymers are, for example, polysulfones, polyethersulfones, polyphenylsulfones, polyetherimides, polyamideimides, which preferably have thermal stability to withstand processing temperatures above 350° C. Suitable fillers are, for example, glass beads, glass fibers, carbon fibers, talc, calcium carbonate, wollastonite and polyamide fibers.
[0092] Suitable colorants are, for example, pigments or dyes, such as titanium dioxide, zinc oxide, carbon black and the like.
[0093] The composition of the invention preferably comprises more than 50% by weight, more preferably more than 75% by weight and particularly preferably more than 90% by weight of amorphous polymer (P), based on the total weight of the composition. The weight of at least one component is generally 0 to 50% by weight, preferably 0 to 25% by weight and particularly preferably 0 to 10% by weight, based on the total weight of the composition. In another embodiment, the composition may be substantially free of the above-mentioned components.
[0094] Another aspect of the invention is an article comprising an amorphous polymer (P). In a preferred embodiment, the article is selected from the group consisting of fittings, pipes, valves, manifolds, aircraft interior panels or components, cookware, medical devices or device components, medical boxes or trays, laboratory animal cages, laboratory equipment, coatings, composite materials, fibers and fabrics.
[0095] Process for preparing an amorphous polymer (P)
[0096] Another aspect of the present invention is a method for preparing an amorphous polymer (P). The above description and preferences for the amorphous polymer (P) apply accordingly to the method for preparing the amorphous polymer (P). In addition, the description and preferences made hereinafter for the method for preparing the amorphous polymer (P) apply accordingly to the amorphous polymer (P).
[0097] Another object of the present invention is a method for converting a reaction mixture (R G ) to prepare an amorphous polymer (P):
[0098] (A1) at least one aromatic dihalogen sulfone compound (D1,1),
[0099] (A2) at least one aromatic dihalogen ketone compound (D2,1),
[0100] (B1) 4,4'-diphenol,
[0101] (C) at least one carbonate component comprising at least 80% by weight of potassium carbonate, based on the reaction mixture (R G ) is based on the total weight of component (C),
[0102] (D) at least one aprotic polar solvent.
[0103] In a preferred embodiment, the method for preparing an amorphous polymer (P) of the present invention comprises the steps of: I) reacting a reaction mixture (R) comprising the above components (A1), (A2), (B1), (C) and (D); G ) for conversion.
[0104] Components (A1), (A2) and (B1) undergo polycondensation reaction.
[0105] Component (D) serves as a solvent, and component (C) serves as a base to deprotonate component (B1) before or during the condensation reaction.
[0106] Reaction mixture (R G ) is understood to mean the mixture used for preparing the amorphous polymer (P) in the process according to the invention. G ) all detailed information given relates to the mixture as it exists before the polycondensation. The polycondensation is carried out during the process according to the invention, wherein the reaction mixture (R G ) is reacted by polycondensation of components (A1), (A2) and (B1) to obtain the target product, an amorphous polymer (P). The mixture containing the target product, the amorphous polymer (P), obtained after polycondensation is also referred to as the product mixture (P GThe product mixture (PG) usually further comprises at least one aprotic polar solvent (component (D)) and a halide. G ) is formed during the conversion of component (C) with component (B1). In the conversion process, first component (C) reacts with component (B1) to deprotonate component (B1). Then, the deprotonated component (B1) reacts with component (A1), whereby a halide is formed. This method is known to those skilled in the art.
[0107] In one embodiment of the present invention, a first amorphous polymer (P1) is obtained in step I). This embodiment is described in more detail below. In this embodiment, the product mixture (P G ) comprises a first amorphous polymer (P1). Then, the product mixture (P G ) usually further comprises at least one aprotic polar solvent (component (D)) and a halide. For the halide, the above details apply.
[0108] Reaction mixture (R G ) are usually reacted simultaneously. The components can be mixed in an upstream step and then reacted. The components can also be fed into a reactor, where they are mixed and then reacted.
[0109] In the process of the present invention, the reaction mixture (R G ) are usually reacted simultaneously in step I). The reaction is preferably carried out in one stage. This means that the deprotonation of component (B1) and the condensation reaction between components (A1), (A2) and (B1) are carried out in a single reaction stage without isolating the intermediate product, for example the deprotonated substance of component (B1).
[0110] Step I) of the process according to the invention is carried out according to the so-called "carbonate method". The process according to the invention is not carried out according to the so-called "hydroxide method". This means that the process according to the invention is not carried out in two stages for separating the phenolate anions.
[0111] It is also preferred that the reaction mixture (R G ) does not contain toluene or chlorobenzene. Particularly preferably, the reaction mixture (R G ) does not contain any substance that forms an azeotrope with water.
[0112] Therefore, another object of the present invention is also such a process, in which the reaction mixture (R G ) does not contain any substance that forms an azeotrope with water.
[0113] The molar ratio of the sum of components (A1), (A2) to component (B1) (ratio (A1+A2) / (B1)) results in principle from the stoichiometry of the polycondensation reaction, which is theoretically carried out with elimination of hydrogen chloride and is determined in a known manner by a person skilled in the art.
[0114] Preferably, the molar ratio of component (B1) to the sum of components (A1) and (A2) is from 0.95 to 1.08, especially from 0.96 to 1.06, most preferably from 0.97 to 1.05.
[0115] Therefore, another object of the present invention is also such a process, in which the reaction mixture (R G ) to the total of components (A1) and (A2) in a molar ratio of 0.97 to 1.08.
[0116] In a preferred embodiment, the reaction mixture (R G ) further comprises up to 15% by weight, more preferably up to 7.5% by weight, particularly preferably up to 2.5% by weight and most preferably up to 1% by weight of further components different from components (A1), (A2), (B1), (C) and (D), based on the reaction mixture (R G ) by total weight.
[0117] In another most preferred embodiment, the reaction mixture (R G ) consists of components (A1), (A2), (B1), (C) and (D).
[0118] Preferably, the conversion in the polycondensation reaction is at least 0.9.
[0119] The process step I) for preparing the amorphous polymer (P) is usually carried out under the conditions of the so-called "carbonate process". This means that the reaction mixture (R G ) is reacted under the conditions of the so-called "carbonate process". The reaction (polycondensation) is usually carried out at a temperature of 80 to 250° C., preferably 100 to 220° C. The upper limit of the temperature is determined by the boiling point of at least one aprotic polar solvent (component (D)) at standard pressure (1013.25 mbar). The reaction is usually carried out at standard pressure. The reaction is preferably carried out for a period of 2 to 12 hours, in particular 3 to 10 hours.
[0120] The amorphous polymer (P) obtained in the process of the invention is present in the product mixture (P G ) can be separated, for example, by precipitation of the product mixture (P G). The precipitated amorphous polymer (P) can then be extracted with water and then dried. In one embodiment of the invention, the precipitate can also be dissolved in an acidic medium. Suitable acids are, for example, organic or inorganic acids, for example carboxylic acids, such as acetic acid, propionic acid, succinic acid or citric acid, and inorganic acids, such as hydrochloric acid, sulfuric acid or phosphoric acid.
[0121] In one embodiment of the present invention, a first amorphous polymer (P1) is obtained in step I). Then, the method of the present invention preferably further comprises the following steps:
[0122] II) reacting the first amorphous polymer (P1) obtained in step I) with an alkyl halide.
[0123] Therefore, another object of the present invention is also such a process, wherein in step I) a first amorphous polymer (P1) is obtained, and wherein the process further comprises the following steps:
[0124] II) reacting the first amorphous polymer (P1) obtained in step I) with an alkyl halide.
[0125] It is clear to the person skilled in the art that the first amorphous polymer (P1) corresponds to the amorphous polymer (P) if step II) is not carried out.
[0126] The first amorphous polymer (P1) is usually a reaction mixture (R G ) is a product of the polycondensation reaction of components (A1), (A2) and component (B1) contained in the mixture. G ) may contain a first amorphous polymer (P1), the product mixture (P G ) in the reaction mixture (R G As mentioned above, the product mixture (P G ) comprises a first amorphous polymer (P1), a component (D) and a halide. When the first amorphous polymer (P1) reacts with an alkyl halide, the product mixture (P G ) may contain a first amorphous polymer (P1).
[0127] The separation of the halides from the first product mixture (P1) can be carried out by any method known to the skilled person, for example by filtration or centrifugation.
[0128] The first amorphous polymer (P1) generally contains terminal hydroxyl groups. In step II), these terminal hydroxyl groups are further reacted with alkyl halides to obtain polyarylene ether sulfone polymer (P). Preferred alkyl halides are in particular alkyl chlorides having a linear or branched alkyl group with 1 to 10 carbon atoms, in particular primary alkyl chlorides, particularly preferably methyl halides, in particular methyl chloride.
[0129] The reaction of step II) is preferably carried out at a temperature of 90° C. to 160° C., in particular 100° C. to 150° C. The time required can vary within a wide range and is generally at least 5 minutes, in particular at least 15 minutes. Preferably, the time required for the reaction of step II) is 15 minutes to 8 hours, in particular 30 minutes to 4 hours.
[0130] A variety of methods can be used to add the alkyl halide. In addition, a stoichiometric amount or an excess of the alkyl halide can be added, the excess being, for example, up to 5 times. In a preferred embodiment, the alkyl halide is added continuously, particularly by continuously introducing in the form of a gas stream.
[0131] In step II), a polymer solution (PL) is usually obtained which comprises the amorphous polymer (P) and the component (D). If the product mixture (P) from step I) is used in step II), G ), the polymer solution (PL) usually also contains halides. The polymer solution (PL) can be filtered after step II). In this way, the halides can be removed.
[0132] Therefore, the present invention also provides a process, wherein in step II) a polymer solution (PL) is obtained, and wherein the process further comprises the following steps:
[0133] III) Filtering the polymer solution (PL) obtained in step II).
[0134] The amorphous polymer (P) obtained in step II) of the present invention can be separated from the polymer solution (PL) by separation in the product mixture (P G ). For example, the separation can be carried out by precipitating the polymer solution (PL) in water or a mixture of water and other solvents. The precipitated amorphous polymer (P) can then be extracted with water and then dried. In one embodiment of the invention, the precipitate can also be dissolved in an acidic medium. Suitable acids are, for example, organic or inorganic acids, such as carboxylic acids, such as acetic acid, propionic acid, succinic acid or citric acid, and inorganic acids, such as hydrochloric acid, sulfuric acid or phosphoric acid.
[0135] Component (A1)
[0136] Reaction mixture (R G ) comprises at least one aromatic dihalogen sulfone compound (D1,1). In the present invention, the term "at least one aromatic dihalogen sulfone compound (D1,1)" is understood to mean exactly one aromatic dihalogen sulfone compound (D1,1) and a mixture of two or more aromatic dihalogen sulfone compounds (D1,1).
[0137] For component (A1), the above statements and preferences regarding the aromatic dihalogen sulfone compound (D1,1) apply correspondingly.
[0138] Component (A2)
[0139] Reaction mixture (R G ) comprises at least one aromatic dihalogen ketone compound (D2,1). In the present invention, the term "at least one aromatic dihalogen ketone compound (D2,1)" is understood to mean exactly one aromatic dihalogen ketone compound (D2,1) and a mixture of two or more aromatic dihalogen ketone compounds (D2,1). For component (A2), the above description and preferences for aromatic dihalogen ketone compounds (D2,1) apply accordingly.
[0140] Component (B1)
[0141] For component (B1), the above descriptions and preferences for at least one aromatic dihydroxy compound (aDHy1) and (aDHy2) apply accordingly. In the present invention, component (B1) is understood to mean exactly one aromatic dihydroxy compound (aDHy1; aDHy2) and a mixture of two or more aromatic dihydroxy compounds (aDHy1; aDHy2). In a preferred embodiment, component (B1) is 4,4'-diphenol.
[0142] Component (C)
[0143] Reaction mixture (R G ) comprises at least one carbonate component as component (C). In the present invention, the term "at least one carbonate component" is understood to mean exactly one carbonate component and a mixture of two or more carbonate components. The at least one carbonate component is preferably at least one metal carbonate. The metal carbonate is preferably anhydrous.
[0144] Alkali metal carbonates and / or alkaline earth metal carbonates are preferred as metal carbonates. At least one metal carbonate selected from sodium carbonate, potassium carbonate and calcium carbonate is particularly preferred as metal carbonate. Potassium carbonate is most preferred.
[0145] For example, component (C) comprises at least 50 wt. %, more preferably at least 70 wt. % and most preferably at least 90 wt. % potassium carbonate, based on the reaction mixture (R G ) is based on the total weight of at least one carbonate component.
[0146] A further object of the present invention is therefore also a process in which component (C) comprises at least 50% by weight of potassium carbonate, based on the total weight of component (C).
[0147] In a preferred embodiment, component (C) consists essentially of potassium carbonate.
[0148] In the present invention, “consisting essentially of . . . ” is understood to mean that component (C) comprises more than 99% by weight, preferably more than 99.5% by weight, particularly preferably more than 99.9% by weight, of potassium carbonate, in each case based on the reaction mixture (R G ) is based on the total weight of component (C).
[0149] In a particularly preferred embodiment, component (C) consists of potassium carbonate.
[0150] Potassium carbonate having a volume weighted average particle size of less than 200 μm is particularly preferred as potassium carbonate. The volume weighted average particle size of potassium carbonate is determined in a suspension of potassium carbonate in chlorobenzene / sulfolane (60 / 40) using a Malvern Mastersizer 2000 Instrument particle size analyzer.
[0151] In a preferred embodiment, the reaction mixture (R G ) does not contain any alkali metal hydroxide or alkaline earth metal hydroxide.
[0152] Component (D)
[0153] Reaction mixture (R G ) comprises at least one aprotic polar solvent as component (D). According to the present invention, “at least one aprotic polar solvent” is understood to mean exactly one aprotic polar solvent as well as a mixture of two or more aprotic polar solvents.
[0154] Suitable aprotic polar solvents are, for example, selected from anisole, dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, N-ethylpyrrolidone, sulfolane and N,N-dimethylacetamide.
[0155] Preferably, component (D) is selected from N-methylpyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide and dimethylformamide. Particularly preferred is N-methylpyrrolidone as component (D).
[0156] A further object of the present invention is therefore also a process in which component (D) is selected from the group consisting of N-methylpyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide and dimethylformamide.
[0157] Preferably, component (D) does not contain sulfolane. Also preferably, the reaction mixture (R G ) does not contain diphenyl sulfone.
[0158] Preferably, component (D) comprises at least 50% by weight of at least one solvent selected from the group consisting of N-methylpyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide and dimethylformamide, based on the reaction mixture (R G ) is based on the total weight of component (D) in the mixture. N-Methylpyrrolidone is particularly preferred as component (D).
[0159] In another preferred embodiment, component (D) consists essentially of N-methylpyrrolidone.
[0160] In the present invention, “essentially consisting of” is understood to mean that component (D) comprises more than 98% by weight, particularly preferably more than 99% by weight, more preferably more than 99.5% by weight of at least one aprotic polar solvent selected from the group consisting of N-methylpyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide and dimethylformamide, wherein N-methylpyrrolidone is preferred.
[0161] In a preferred embodiment, component (D) consists of N-methylpyrrolidone. N-methylpyrrolidone is also known as NMP or N-methyl-2-pyrrolidone. Example
[0162] Components used
[0163] DCDPS: 4,4'-dichlorodiphenyl sulfone,
[0164] DCBPO: 4,4'-dichlorobenzophenone,
[0165] BP: 4,4'-biphenol,
[0166] Potassium carbonate: K2CO3; anhydrous; volume average particle size is 34.5μm,
[0167] NMP: N-methylpyrrolidone,
[0168] PPSU: Polyphenylsulfone ( P 3010)
[0169] General method steps
[0170] The viscosity numbers of the polymers are determined in accordance with DIN EN ISO 1628-1 at 25° C. in 1% solution in NMP.
[0171] At room temperature (25° C.), the polymer was isolated by dropping a solution of the polymer in NMP into deionized water. The drop height was 0.5 m and the flow rate was about 2.5 l / h. The obtained beads were then extracted with water at 85° C. (water flow rate of 160 l / h) for 20 hours. The beads were dried at 150° C. for 24 h (hours) under reduced pressure (<100 mbar) to a residual moisture of less than 0.1% by weight.
[0172] The amorphous polymer (P) obtained was pelletized by means of a ZSK 18 extruder. At a rotation speed of 300 rpm, the throughput was 2.5 kg / h, the temperature of the melt was measured at the melt with an insertion thermometer and was below 385°C.
[0173] The obtained pellets were injection molded at a mass temperature of 370° C. and a mold temperature of 140° C. to obtain ISO rods (80*10*4 mm*mm*mm) and S2 tensile rods.
[0174] The melt stability of the samples was measured using a capillary rheometer over 60 min at a mass temperature of 400 °C. Therefore, every five minutes at 55 s -1 The apparent viscosity of the melt was measured at an apparent shear rate of . The melt stability is the quotient of the apparent viscosity after 60 minutes divided by the apparent viscosity after 5 minutes. The results are shown in Table 1.
[0175] The glass transition temperature (T g ) and the melting point were determined by differential scanning calorimetry DSC in a double heating cycle as described above at a heating rate of 20 K / min.
[0176] The content of benzophenone groups is determined by 1 H-NMR was measured using CDCl 3 as a solvent.
[0177] The resistance of the polymer to hydraulic fluids, gasoline and / or fuels is determined as LD4 (58 wt% tributyl phosphate, 20 to 30 wt% dibutylphenyl phosphate, 5 to 10 wt% butylphenyl phosphate, 1 to 5 wt% 2,6-di-tert-butyl-p-cresol, less than 10 wt% carboxylic acid esters). The S2-tie rods were stored at 24 hours in LD4. In each case, two S2 tie rods were bent to a bending radius of 132 mm using a template before storage. Using a camera, one picture was taken every minute to determine the time until rupture.
[0178] Polymer V1
[0179] In a 4-liter glass reactor equipped with a thermometer, an inlet tube and a Dean-Stark water trap, 522.63 g (1.82 mol) of DCDPS, 372.41 g (2.00 mol) of 4,4′-dihydroxybiphenyl, 50.22 g (0.20 mol) of 4,4′-dichlorobenzophenone and 304.05 g (2.20 mol) of potassium carbonate having a volume average particle size of 34.5 μm were suspended in 1152 ml of NMP under a nitrogen atmosphere.
[0180] The mixture was heated within one hour to 190° C. In the following, the reaction time is understood to be the time during which the reaction mixture was kept at 190° C. The water formed in the reaction was removed continuously by distillation, and the NMP lost was replaced.
[0181] At 190 ° C, the reaction was continued for another 5 hours, then 1500 ml of NMP was added to the reactor, and the temperature of the suspension was adjusted to 135 ° C (consuming 10 minutes). Then, methyl chloride was added to the reactor for 60 minutes. Then nitrogen was purged through the suspension for another 30 minutes. The solution was then cooled to 80 ° C and then transferred to a pressure filter to separate the potassium chloride formed in the reaction by filtration. The resulting polymer solution was then precipitated in water, the resulting polymer beads were separated, and then extracted with hot water (85 ° C) for 20 hours. The beads were then dried at 120 ° C under reduced pressure (<100 mbar) for 24 hours.
[0182] Amorphous polymer (P)2
[0183] In a 4-liter glass reactor equipped with a thermometer, an inlet tube and a Dean-Stark water trap, 508.28 g (1.77 mol) of DCDPS, 372.41 g (2.00 mol) of 4,4′-dihydroxybiphenyl, 62.78 g (0.25 mol) of 4,4′-dichlorobenzophenone and 304.05 g (2.20 mol) of potassium carbonate having a volume average particle size of 34.5 μm were suspended in 1152 ml of NMP under a nitrogen atmosphere.
[0184] The mixture was heated to 190° C. within one hour. In the following, the reaction time is understood to mean the time during which the reaction mixture was kept at 190° C. The water formed in the reaction was removed continuously by distillation, and the NMP lost was replaced.
[0185] At 190 ° C, the reaction was continued for another 5 hours, then 1500 ml of NMP was added to the reactor, and the temperature of the suspension was adjusted to 135 ° C (consuming 10 minutes). Then methyl chloride was added to the reactor for 60 minutes. Then nitrogen was purged through the suspension for another 30 minutes. The solution was then cooled to 80 ° C and then transferred to a pressure filter to separate the potassium chloride formed in the reaction by filtration. The resulting polymer solution was then precipitated in water, the resulting polymer beads were separated, and then extracted with hot water (85 ° C) for 20 hours. The beads were then dried at 120 ° C under reduced pressure (<100 mbar) for 24 hours.
[0186] Amorphous polymer (P)3
[0187] In a 4-liter glass reactor equipped with a thermometer, an inlet tube and a Dean-Stark water trap, 493.92 g (1.72 mol) of DCDPS, 372.41 g (2.00 mol) of 4,4′-dihydroxybiphenyl, 75.33 g (0.3 mol) of 4,4′-dichlorobenzophenone and 304.05 g (2.20 mol) of potassium carbonate having a volume average particle size of 34.5 μm were suspended in 1152 ml of NMP under a nitrogen atmosphere.
[0188] The mixture was heated within one hour to 190° C. In the following, the reaction time is understood to be the time during which the reaction mixture was kept at 190° C. The water formed in the reaction was removed continuously by distillation, and the NMP lost was replaced.
[0189] At 190°C, the reaction was continued for another 5.5 hours, then 1500ml of NMP was added to the reactor, and the temperature of the suspension was adjusted to 135°C (consuming 10 minutes). Chloromethane was then added to the reactor for 60 minutes. Nitrogen was then purged through the suspension for another 30 minutes. The solution was then cooled to 80°C and then transferred to a pressure filter to separate the potassium chloride formed in the reaction by filtration. The resulting polymer solution was then precipitated in water, the resulting polymer beads were separated, and then extracted with hot water (85°C) for 20 hours. The beads were then dried at 120°C under reduced pressure (<100mbar) for 24 hours.
[0190] Amorphous polymer (P)4
[0191] In a 4-liter glass reactor equipped with a thermometer, an inlet tube and a Dean-Stark water trap, 465.22 g (1.62 mol) of DCDPS, 372.41 g (2.00 mol) of 4,4′-dihydroxybiphenyl, 100.44 g (0.40 mol) of 4,4′-dichlorobenzophenone and 304.05 g (2.20 mol) of potassium carbonate having a volume average particle size of 34.5 μm were suspended in 1152 ml of NMP under a nitrogen atmosphere.
[0192] The mixture was heated to 190° C. within one hour. In the following, the reaction time is understood to mean the time during which the reaction mixture was kept at 190° C. The water formed in the reaction was removed continuously by distillation, and the NMP lost was replaced.
[0193] At 190 ° C, the reaction was continued for another 6 hours, then 1500 ml of NMP was added to the reactor, and the temperature of the suspension was adjusted to 135 ° C (consuming 10 minutes). Then methyl chloride was added to the reactor for 60 minutes. Then nitrogen was purged through the suspension for another 30 minutes. The solution was then cooled to 80 ° C and then transferred to a pressure filter to separate the potassium chloride formed in the reaction by filtration. The resulting polymer solution was then precipitated in water, the resulting polymer beads were separated, and then extracted with hot water (85 ° C) for 20 hours. The beads were then dried at 120 ° C under reduced pressure (<100 mbar) for 24 hours.
[0194] Polymer V5
[0195] In a 4-liter glass reactor equipped with a thermometer, an inlet tube and a Dean-Stark water trap, 450.86 g (1.57 mol) of DCDPS, 372.41 g (2.00 mol) of 4,4′-dihydroxybiphenyl, 113.00 g (0.45 mol) of 4,4′-dichlorobenzophenone and 304.05 g (2.20 mol) of potassium carbonate having a volume average particle size of 34.5 μm were suspended in 1152 ml of NMP under a nitrogen atmosphere.
[0196] The mixture was heated to 190° C. within one hour. In the following, the reaction time is understood to mean the time during which the reaction mixture was kept at 190° C. The water formed in the reaction was removed continuously by distillation, and the NMP lost was replaced.
[0197] At 190 ° C, the reaction was continued for another 6 hours, then 1500 ml of NMP was added to the reactor, and the temperature of the suspension was adjusted to 135 ° C (consuming 10 minutes). Then methyl chloride was added to the reactor for 60 minutes. Then nitrogen was purged through the suspension for another 30 minutes. The solution was then cooled to 80 ° C and then transferred to a pressure filter to separate the potassium chloride formed in the reaction by filtration. The resulting polymer solution was then precipitated in water, the resulting polymer beads were separated, and then extracted with hot water (85 ° C) for 20 hours. The beads were then dried at 120 ° C under reduced pressure (<100 mbar) for 24 hours.
[0198] Table 1:
[0199]
[0200] *The solution is not completely homogenous
[0201] As can be seen from the results shown in Table 1, if the content of benzophenone units (BPO units) is below 10 mol%, no improvement in Skydrol tolerance can be detected. If the content of BPO-based units is above 20 mol%, the product cannot be isolated because filtration of the suspension requires more than 24 hours. If a small amount of material is precipitated and washed, there may be no homogeneous NMP solution for VN measurement. In CDCl3 (H-NMR), the product is also not completely soluble, but the spectrum obtained enables the determination of the content based on BPO units. The small amount of product isolated from test V5 was melt-pressed into a film at 320°C. Although the film thickness is only 50 μm, the sample is also opaque.
Claims
1. An amorphous polymer (P) comprising: The following chain segment (S1) The following chain segment (S2) The following chain segment (S3) wherein the amorphous polymer (P) comprises: 80.1 to 89 mol% of segment (S1), and 11 to 19.9 mol% of segments (S2), Based on the total number of moles of the segments (S1) and (S2) contained in the amorphous polymer (P); wherein the ratio of the number of moles of the segment (S1) contained in the amorphous polymer (P) to the number of moles of the segment (S2) is 4.02 to 8.09; The amorphous polymer (P) comprises repeating units (RU1) and (RU2), wherein the repeating unit (RU1) is obtainable by a reaction between at least one aromatic dihalogen compound (D1,1) comprising a segment (S1) and at least one aromatic dihydroxy compound (aDHy1), and wherein the repeating unit (RU2) is obtainable by a reaction between at least one dihalogen compound (D2,1) comprising a segment (S2) and at least one aromatic dihydroxy compound (aDHy2), wherein the amorphous polymer (P) does not comprise any other repeating units other than the repeating units (RU1) and (RU2). 2 . The amorphous polymer (P) according to claim 1 , wherein the aromatic dihalogen compound (D1,1) is at least one compound selected from the group consisting of 4,4′-dihalogendiphenylsulfone and 4,4′-bis[(4-chlorophenyl)sulfonyl]-1,1′-biphenyl.
3. The amorphous polymer (P) according to claim 1, wherein the polydispersity (Q) of the amorphous polymer (P) is from 2.0 to ≤5.
0.
4. The amorphous polymer (P) according to claim 1, wherein the weight average molecular weight M of the amorphous polymer (P) is W 30,000 to 120,000 g / mol, measured using gel permeation chromatography (GPC), wherein in the measurement, dimethylacetamide (DMAc) is used as a solvent, and narrow distribution polymethyl methacrylate is used as a standard. 5 . The amorphous polymer (P) according to claim 1 , wherein the dihalogen compound (D2,1) is a 4,4′-dihalogen benzophenone. 6 . The amorphous polymer (P) according to claim 1 , wherein the aromatic dihydroxy compound (aDHy1) and / or (aDHy2) is 4,4′-diphenol.
7. Amorphous polymer (P) according to claim 1, wherein the repeating unit (RU1) is obtained by reaction of the monomers 4,4'-dichlorodiphenyl sulfone and 4,4'-diphenol.
8. Amorphous polymer (P) according to claim 1, wherein the repeating unit (RU2) is obtained by reaction of the monomers 4,4'-dichlorobenzophenone and 4,4'-diphenol.
9. A method for preparing an amorphous polymer (P) according to claim 1, comprising: G ) to transform: (A1) at least one aromatic dihalogen sulfone compound (D1,1), (A2) at least one aromatic dihalogen ketone compound (D2,1), (B1) 4,4'-diphenol, (C) at least one carbonate component comprising at least 80% by weight of potassium carbonate, based on the reaction mixture (R G ) is based on the total weight of component (C), (D) at least one aprotic polar solvent.
10. A composition comprising the amorphous polymer (P) according to claim 1 or the amorphous polymer (P) prepared according to claim 9.
11. Article comprising the amorphous polymer (P) according to claim 1 or the amorphous polymer (P) prepared according to claim 9 or the composition according to claim 10.
12. The article of claim 11, wherein the article is selected from the group consisting of fittings, pipes, valves, manifolds, aircraft interior panels or components, cookware, medical devices or device components, laboratory equipment, coatings, composites, fibers, and fabrics.
13. The article of claim 11 or 12, wherein the article is transparent.
14. The article of claim 12, wherein the article is selected from the group consisting of a medical box or tray and a laboratory animal cage.
Citation Information
Patent Citations
High temperature resistant thermoplastic moulding masses with improved melt stability
EP0297363A2
Polyphenyl sulfone ketone copolymers
EP2225328A1
Sulfonic group-containing photocrosslinkable polymer, sulfonic group-containing photocrosslinkable polymer composition, polyelectrolyte film, crosslinked polyelectrolyte film, polyelectrolyte film / electrode assembly, fuel cell and application thereof
JP2008037897A